Technical Efficiency of Indonesia’s Sugar Manufacturing Industry: Based on DEA-Bootstrap Approach - Fifi Ulid Khoiro Taufiqo; Dyah Wulan Sari; Ignatia Martha Hendrati (Jurnal Ekonomi dan Studi Pembangunan, 2021)
This study aims to measure the technical efficiency of companies in the sugar industry in Indonesia and determine the factors that influence the technical efficiency scores of these companies. The data was used in the form of time series for 2010-2014 with observations of 340 companies. The Bootstrap data envelopment method with the assumption of a return to scale variables and input orientation is used to measure the company’s technical efficiency score. The results will be analyzed further as the dependent variable with Tobit regression for the technical efficiency determinant analysis stage. Based on the analysis results, the average score of the technical efficiency of the sugar industry is 0.67. Based on Tobit’s estimation, the location factor is significant to the technical efficiency score, while the export, import, company ownership, market concentration, and firm size are not significant Keywords: Data Envelopment Analysis Bootstrap; Sugar Industry; Technical Efficiency, Tobit RegressionJEL Classification: O14, L66